2019
DOI: 10.31234/osf.io/k7na5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When the Personal is Political: Ethnic Identity, Ally Identity, and Political Engagement Among Indigenous People and People of Color

Abstract: Objectives: During an increasingly hostile social and political climate for ethnic-racial minorities, psychologists have begun to question the extent to which Indigenous People and People of Color (IPPOC) see one another as in the same boat (Rivas-Drake & Bañales, 2018). Consequently, the present mixed-methods study examines allyship as a potential politicized collective identity and its associations with ethnic identity, personality traits, and political engagement among IPPOC. Method: The present st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…More recently, Pinetta et al (2020) found that ethnic-racial exploration, but not resolution, was positively associated with Latinx early adolescents' expectations that they would be involved in their communities. Among Indigenous and other college students of color, more ERI exploration was also positively associated with students' engagement in political actions and a stronger sense of themselves as allies to other communities of color (Fish et al, 2021). In addition, Bañales et al (2020) found that increases in ERI resolution were associated with increased civic and community orientations among a pooled sample of Latinx and Black early adolescents.…”
Section: Eri As a Direct Promotive Predictor Of Positive Youth Developmentmentioning
confidence: 92%
“…More recently, Pinetta et al (2020) found that ethnic-racial exploration, but not resolution, was positively associated with Latinx early adolescents' expectations that they would be involved in their communities. Among Indigenous and other college students of color, more ERI exploration was also positively associated with students' engagement in political actions and a stronger sense of themselves as allies to other communities of color (Fish et al, 2021). In addition, Bañales et al (2020) found that increases in ERI resolution were associated with increased civic and community orientations among a pooled sample of Latinx and Black early adolescents.…”
Section: Eri As a Direct Promotive Predictor Of Positive Youth Developmentmentioning
confidence: 92%
“…In this paper, we articulate theoretical mechanisms by which Latinx youth may develop anti‐racist identities and engage in anti‐racist actions on behalf of their own ethnic/racial communities and other marginalized communities oppressed by white supremacy. To do so, we draw on theory and research on ERI (Umaña‐Taylor et al., 2014), intersectionality (Crenshaw, 2017), liberation psychology (e.g., Comas‐Díaz & Torres Rivera, 2020), critical consciousness, and sociopolitical development theories (Freire, 1974; Watts et al., 2003), and allyship (e.g., Fish et al., 2021) to understand the psychological processes necessary for Latinx youth to develop anti‐racist identities and actions. We weave these literatures together to present a theoretical model of Latinx youth’s anti‐racist identities and actions (see Figure 1).…”
Section: Figurementioning
confidence: 99%
“…Cross-group allyship—“when a person of one social identity group...stands up in support of members of another social identity group who experiences discrimination or is treated unfairly” (Fish et al, 2020, pg. 5)—is an important piece of the puzzle for advancing positive intergroup relations among minoritized groups.…”
Section: What Develops?mentioning
confidence: 99%
“…But an important question remains: How do ethnic-racial identities support or hinder allyship across distinct types of marginalization? Drawing on Edwards’ (2006) conceptualization of ally identity , Fish and colleagues (2020) examined beliefs about the role of privilege, oppression, and power as well as behaviors that demonstrate the capacity to be allies to other racially or culturally marginalized groups among 18-year-old students in their first year of college who identified either as Asian, Black or African, Latinx, Middle Eastern and North African (MENA), Native American Indian, or mixed ethnicity. They examined allies’ (a) belief that it was important for the outgroup to know they cared about them and the need to work to correct injustice and (b) behaviors that demonstrated they support, use their power to protect, and work with other groups to improve their conditions.…”
Section: What Develops?mentioning
confidence: 99%
See 1 more Smart Citation